SDG Pulse 2019 - United Nations Conference on Trade; Development (United Nations, 2019)
This first edition of the SDG Pulse illustrates in a very concrete way how UNCTAD is contributing to the 2030 Agenda. The report not only presents statistical updates for the indicators for which UNCTAD is a custodian or co-custodian, but it also presents a range of other complementary indicators that provide a wider context and more nuance to these complex topics. This report also presents some case studies from UNCTAD’s capacity development programme from a statistical perspective – presenting our activities and successes in hard numbers. These case studies are important as they illustrate the Results Based Management approach being adopted by UNCTAD – helping us to improve our responsiveness and accountability to member states. Finally, this report will every year, highlight a thematic issue of immediate relevance. This year’s theme addresses the many faces of inequality. In particular, to discuss how developments with regard to access to data and information may be creating new dimensions of inequality.